THE DYNAMICS OF DISHONESTY IN INTERPERSONAL COMMUNICATION AGAINST THE TRUST OF STUDENT COUPLES IN THE AREA OF RT 02 RW 14 RAWAMANGUN - Fani Anisa Putri; RR Roosita Cindrakasih (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study aims to determine the dynamics of dishonesty in interpersonal communication toward the trust of college student couples in RT 02 RW 14 Rawamangun. Dishonesty in relationships is not only related to the delivery of inaccurate information but also includes openness, communication patterns, and how couples deal with conflicts. This study uses a qualitative approach with a descriptive method. Data collection was conducted through in-depth interviews with three college student couples who had experiences related to dishonesty in romantic relationships and one triangulator as supporting research data. The results show that dishonesty appears in various forms, such as hiding information, reducing openness, and communicating with other parties without the partner’s knowledge. Such behavior affects the dynamics of interpersonal communication and causes changes in the level of trust within the relationship. Decreased trust can lead to conflicts, suspicion, and changes in communication patterns between partners. This study shows that openness and effective communication play an important role in maintaining the quality of romantic relationships.